E-CADHERIN-A SURROGATE MARKER AND ITS RELATION TO OTHER BIOMARKERS IN EARLY STAGES OF DIABETIC NEPHROPATHY IN EASTERN PROVINCE OF SAUDI ARABIAN POPULATION - Moattar Raza Rizvi (Journal of Global Pharma Technology, 2016)
Background: At present, it is very arduous to reliably envisage which, and when, diabetic patients will developnephropathy and progress to kidney failure. Therefore, preventing diabetic nephropathy or delaying the disease progression bysearching for novel biomarkers is very important. Objective: Determination of diagnostic and prognostic significance of solubleE-cadherin (sE-cadherin) and cystatin C as novel biomarkers of diabetic nephropathy in type 2 diabetic (T2D) Saudi patients.Patients and Methods: Type 2 diabetic patients (n=50) with urinary albumin excretions (UAE) > 300 mg/day (n=16)macroalbuminuria, between 30-300 mg/day (n=14) microalbuminuria and without urinary albumin excretions (UAE < 30 mg/24h) (n=20) normoalbuminuria and 15 controls were enrolled in the study. sE-cadherin, Serum Cystatin C, beta2-microglobulin,urinary microalbumin levels, and creatinine clearances were determined in all groups. Results: There was significant increasein the values of fasting blood sugar(FBS), serum creatinine, NAG, b-microglobulin, Hb1Ac in different groups. There was nosignificant change of Hb1Ac and serum creatinine between diabetic mellitus (DM) with normalbuminuria and diabeticnephropathy with microalbuminuria. The diabetic control and DM group presented with no significant change in E-cadherin(p=ns), however there was significant change of E-cadherin between DM with normoalbuminuria and diabetic nephropathy withmicroalbuminuria (p<0,001) and diabetic nephropathy with macroalbuminuria. Serum creatinine, FBS, cystatin C and Hb1Acwere known predictors of E-cadherin as extracted from regression model [Y(E-cadherin)= -1792.2+ 0.51(S.Creatinine)+0.47(FBS)+0.30(Cystatin C)-0.24(HbA1c)]. Cystatin C was significantly increased in DM as compared to diabetic control (p<0,001),however there was no change between DM normoalbuminuria and diabetic nephropathy microalbuminuria (p=ns). Furtherthere was significant increase in the values of Cystatin C in diabetic nephropathy with macroalbuminuria as compared todiabetic nephropathy with microalbuminuria and normoalbuminuria. Linear regression model of cystatin showed only Ecadherinand b-microglobulin as independent variables [Y (cystatin C) = 0.301+0.559(E-cadherin) + 0.363(β-microglobulin)].Conclusion: In conclusion, this study demonstrated that E-cadherin and cystatin C might play an important role in thedevelopment of early diabetic nephropathy and their measurement might become a useful and noninvasive marker thancreatinine or β2-MG for early incipient diabetic nephropathy as well as for the evaluation of renal involvement of T2D patients.